2020
DOI: 10.1613/jair.1.11864
|View full text |Cite
|
Sign up to set email alerts
|

The Parameterized Complexity of Motion Planning for Snake-Like Robots

Abstract: We study the parameterized complexity of a variant of the classic video game Snake that models real-world problems of motion planning. Given a snake-like robot with an initial position and a final position in an environment (modeled by a graph), our objective is to determine whether the robot can reach the final position from the initial position without intersecting itself. Naturally, this problem models a wide-variety of scenarios, ranging from the transportation of linked wagons towed by a locomotor at an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Snake is typically played on grid graphs, and it is known to be PSPACE-complete to determine whether the Snake can reach a specific goal state from a given start state on generalized grid graphs [4]. Independently of our work, Gupta et al [7] have found that reconfiguring snakes (paths that can move only unidirectionally) is fixed-parameter tractable in the length of the path, analogously to our Theorem 1. Fig.…”
Section: Related Workmentioning
confidence: 84%
“…Snake is typically played on grid graphs, and it is known to be PSPACE-complete to determine whether the Snake can reach a specific goal state from a given start state on generalized grid graphs [4]. Independently of our work, Gupta et al [7] have found that reconfiguring snakes (paths that can move only unidirectionally) is fixed-parameter tractable in the length of the path, analogously to our Theorem 1. Fig.…”
Section: Related Workmentioning
confidence: 84%
“…It would be also interesting to know whether Directed Path Reconfiguration and Directed Path Sliding are fixed-parameter tractable (FPT) parameterized by the length of input paths. Although the undirected counterparts are known to be FPT [3,4], it would be difficult to apply their techniques directly to our cases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they showed that if S(G) consists of all trees in G, every instance of the corresponding reconfiguration problem is a yes-instance unless the two input trees have different numbers of edges. Motivated by applications in motion planning, Biasi and Ophelders [1], Demaine et al [3], and Gupta et al [4] studied some variants of reconfiguring undirected paths and showed that these problems are PSPACE-complete, while they are fixed-parameter tractable (FPT) when parameterized by the length of input paths.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, we believe that more subtle underlying parameters need to be considered. Previous positive results that employ parameterized complexity in discrete motion planning problems [1,17] provide some encouragement.…”
Section: Future Workmentioning
confidence: 95%